Resource Discovery in Grid Systems: a Survey - Hameurlain, Abdelkader; Erciyeş, Kayhan; Çokuslu, Deniz; Çokuslu, Deniz; Erciyeş, Kayhan (Inderscience Enterprises Ltd., 2010)
Resource Discovery (RD) is one of the key issues in successful Grid systems. Yet, new methodologies for RD are constantly researched owing to the dynamicity, heterogeneity and large-scale characteristics of Grids. Recently, synergy and convergence between Grid, Agent and Peer-to-Peer (P2P) systems were pointed out clearly. This paper provides a survey and a qualitative comparison of the most promising approaches (P2P techniques and agent systems) for RD. Viability of Grid systems relies mainly on efficient integration of P2P techniques and mobile agent (MA) systems to bring scaling and decentralised control properties to Grids.
Keywords: Grid systems; Mobile agents; P2P techniques; Resource Discovery